Kinetic analysis of instep and side-foot kick in female and male soccer players - Sakamoto, K.; Numazu, N.; Hong, S.; Asai, T. (Procedia Engineering, 2016)
The purpose of this study was to identify the kinetics of instep and side-foot kicks for female and male soccer players to understand the common and different mechanics underlying the two kicks. 6 female and 6 male soccer players performed maximal instep and side-foot kicks. Their motions and ground reaction forces were recorded by a motion capture system (250 Hz) and a force platform (1000 Hz). The ball velocity of the instep kick (22.5 ± 1.0 m/s for female players, 27.9 ± 1.3 m/s for male players) was significantly higher than that of the side-foot kick (21.5 ± 1.0 m/s for female players, 26.9 ± 1.3 m/s for male players). Significant differences were also observed between the two kicks of female players for the value of hip flexion/extension torque. Moreover, significant differences were also observed between the female and male players for the value of hip adduction/abduction torque for side-foot kick. These results indicated that to enhance such hip torques is one of the technical elements that could be improved to increase ball velocity of side-foot kick in female players.